Confinement Effects of a Noble Gas Dimer Inside a Fullerene Cage: Can It Be Used as an Acceptor in a DSSC? - Paul, Debolina; Dua, Harkishan; Sarkar, Utpal (Frontiers in Chemistry, 2020)
A detailed density functional theory investigation of He2 encapsulated fullerene C36 and C40 has been presented here. When confinement takes place, He-He bond length shortens and a non-covalent type of interaction exists between two He atoms. Energy decomposition analysis shows that though an attractive interaction exists in free He2, but when it is confined inside the fullerenes, repulsive interaction is observed which is due to the presence of dominant repulsive energy term. Fullerene C40, with greater size makes the incorporation of He2 much easier than C36 as confirmed from the study of boundary crossing barrier. In addition, we have studied the possibility of using He2 incorporated fullerene as acceptor material in dye-sensitized solar cell (DSSC). Based on the highest energy gap, He2@C40 and bare C40 fullerenes are chosen for these purpose. Dye constructed with He2@C40 as an acceptor has the highest light-harvesting efficiency and correspondingly will possess the maximum short circuit current as compared to pure C40 acceptor.